INTERNATIONAL EXPERIENCE OF USING GIS IN POPULATION CENSUS: EXPERIENCE FOR UKRAINE - Заставецька, Леся; Заставецький, Тарас; Семеген, Оксана (SWorldJournal, 2023)
The work examines the international experience of using GIS technologies for population censuses. When applying this technology, three main stages are observed: preparatory (in which the database for the census is formed), the main stage – the actual cen